The influence of corporate social responsibility(CSR) and irresponsibility(CSIR) on the brand from the customer perspective - Chen, Ning-xin (2017)
Responsibility issues have increasingly been the concerns in the business context. And the target of this thesis is to describe and evaluate how the company’s CSR and CSIR activities are influencing its customer-based brand. And this research focuses on the customer perception of socially responsible and irresponsible corporate behavior with brands. In the thesis, the literature on the CSR and CSIR issues as well as brand review are presented to provide a theoretical framework and establish a relationship between customer preferences and responsible actions. CSR awareness, significance, and transferability are three aspects to investigate the impacts on the brand.